2005
DOI: 10.1074/jbc.m503396200
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in O-linked β-N-Acetylglucosamine Protein Modification Cause Severe Defects in Mitotic Progression and Cytokinesis

Abstract: The dynamic modification of nuclear and cytoplasmic proteins with O-linked ␤-N-acetylglucosamine (O-GlcNAc) is a regulatory post-translational modification that is rapidly responsive to morphogens, hormones, nutrients, and cellular stress. Here we show that O-GlcNAc is an important regulator of the cell cycle. Increased O-GlcNAc (pharmacologically or genetically) results in growth defects linked to delays in G 2 /M progression, altered mitotic phosphorylation, and cyclin expression. Overexpression of O-GlcNAca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
297
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(319 citation statements)
references
References 66 publications
20
297
0
Order By: Relevance
“…Six different sxc alleles were used in the current study. The origins of the EMS-induced alleles, sxc 1 , sxc 3 , sxc 4 , and sxc 5 , are described in Ingham (8); sxc 1 was induced on a second chromosome bearing NC130 , an EMS-induced allele obtained from the Bloomington Stock Center, was generated more recently using a second chromosome bearing the markers cn and bw (32); its status as an sxc allele was confirmed by complementation (D. Sinclair, unpublished results). sxc 2637 , also obtained from the Bloomington Stock Center, was generated in an extensive P-element-based gene disruption study (33) and was originally designated l (2)02637.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six different sxc alleles were used in the current study. The origins of the EMS-induced alleles, sxc 1 , sxc 3 , sxc 4 , and sxc 5 , are described in Ingham (8); sxc 1 was induced on a second chromosome bearing NC130 , an EMS-induced allele obtained from the Bloomington Stock Center, was generated more recently using a second chromosome bearing the markers cn and bw (32); its status as an sxc allele was confirmed by complementation (D. Sinclair, unpublished results). sxc 2637 , also obtained from the Bloomington Stock Center, was generated in an extensive P-element-based gene disruption study (33) and was originally designated l (2)02637.…”
Section: Methodsmentioning
confidence: 99%
“…S2 and S3). The missense allele sxc 4 does show an immunoreactive protein of the expected size for OGT, yet enzyme activity is nearly completely absent (Figs. S2 and S3).…”
Section: Mutations In the Pcg Gene Sxc Show Corresponding Lesions In mentioning
confidence: 99%
“…PUGNAc is suitable for use in cells (10-100 μM, 4-18 h) and in animals (50 mg/kg, 4-12 h) ; however, prolonged use (>36 h) can lead to cell cycle defects (Slawson et al 2005). While widely used, recent evidence demonstrates that PUGNAc can also inhibit other lysosomal glycosidases including HexA and HexB (Macauley et al 2005;Ficko-Blean et al 2008), suggesting that PUGNAc may have effects on other cellular pathways aside from O-GlcNAcylation.…”
Section: Murine Models and The Ogt F/ymer-cre-2a-gfp Cell Linementioning
confidence: 99%
“…Techniques such as over expression of OGT (Zachara et al 2004b), OGlcNAcase (Slawson et al 2005), and GFAT (Chen et al 1997;Marshall et al 2004;James et al 2000) by both transient transfection and viral transduction have been successful, as has reducing the expression of these enzymes using RNA interference (Zachara et al 2004b;Ngoh et al 2009a;Hsieh et al 2012). OGT has also been overexpressed using a tetracycline-inducible OGT stably expressed in HeLa cells, although for effective overexpression a histone deacetylase inhibitor was included with the tetracycline for appropriate regulation of OGT (Marshall et al 2003).…”
Section: In Vitro and In Vivo Modulation Of O-glcnac Levelsmentioning
confidence: 99%
“…Knockouts of OGT are embryonic and stem cell lethal (44), and conditional knockouts of OGT in various tissues have not been fully completed (45). Overexpression of OGA induces a mitotic exit phenotype (46), suggesting that it too may perform essential functions. We originally identified C. elegans OGT (25) and have shown that knockouts of ogt-1 in the nematode, although viable and fertile, have effects on insulin-like signaling (25,26).…”
mentioning
confidence: 99%